Heart physiology : from heart to circulation - Opie, Lionel H (Lippincott Williams-Wilkins, 2004)
Univ. of Cape Town, Africa. Presents the fundamentals of cardiac function and integrates cellular and subcellular elements of cardiovascular physiology in the analysis of physiologic and pathophysiologic responses. Features new material on cell signalling and more than 300 diagrams and illustrations. Previous edition: c1998. DNLM: Heart--physiology.
Keywords: buňky; Cells; kardiovaskulární fyziologické jevy; srdce; Cardiovascular Physiological Phenomena; kardiologie; Heart